Perfil sistêmico e de saúde bucal de idosos internados em uma Unidade de Terapia Intensiva em Brasília - DF - Félix, Rodrigo Alexandre (2021)
Aim: Assessing the systemic condition and oral health of elderly patients hospitalized in an intensive care unit. Methodology: Observational and descriptive study based on cross-sectional design, focused on assessing the systemic conditions and oral health of a convenience sample comprising 78 conscious elderly patients. General and systemic data were collected through the analysis of patients’ medical records and by assessing their oral cavity – this procedure was carried out by a single calibrated examiner. Descriptive data analysis was performed in IBM SPSS 23 software (2015), at 5% significance level. The non-parametric Mann-Whitney U test was used to compare variables related to oral health status and comorbidities and tongue coating/biofilm (TC), as an ordinal qualitative variable. The Mann-Whitney U test showed better statistical power in comparison to the Chi-square test, with a significance level of 5%. Results: All elderly patients were awake at oral health assessment time; their average age was 77.69 years and most of them were men (51.28%). Postoperative conditions (23.08%) and heart issues (20.51%) were the main reasons for hospitalization in the ICU. Hypertension (69.23%) was the most prevalent comorbidity; it was followed using anticoagulants (57.69%) and antimicrobials (53.85%). Most patients (64.10%) did not receive oral care and 29.49% of them received it only once. Most patients (57.69%) wore dental prosthesis, the presented average DMFT index of 23.74 (average missing teeth value of 17.44) and tongue coating (71.79%); oral hygiene during hospitalization was considered unsatisfactory (84.62%). Elderly with heart diseases (p=0.0037) have more tongue coating compared to other comorbidities. In postoperative situations, the elderly are submitted to anticoagulants (p=0.012); patients with heart alterations are submitted to the action of antibiotics (p=0.009) and other medications (p=0.005). Those with an infection of any origin were under the action of antibiotics (p=0.001). There was no statistical significance between comorbidities and DMFT index, use of medication and comorbidities (arterial pressure, stroke, pulmonary alterations, orthopedic origin and others) and cleaning frequency and types of dental prostheses. Conclusion: Elderly individuals hospitalized in the investigated ICU mostly were men, presented heart disorders and were subjected to anticoagulants and antimicrobials during hospitalization. Hospitalized elderly’s oral conditions were featured by poor oral hygiene, presence of TC and edentulism. It is necessary to implement a guideline focusing on oral health promotion activities in this ICU.